ØªÙ†ÙÙŠØ° ØªØ¯Ø±ÙŠØ³ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© - Sumari mawardi; Binti Baruroh (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2021)
The objectives of this study are: a) to describe learning reading skills in terms of planning, implementation, in terms of evaluation and implementation problems in madrasas, darul Alquran in Bloksno Narathiwat Thailand 2012/2013 academic year. The method used in this research is descriptive qualitative method, in collecting data by observation, interviews and documentation. Data analysis: data collection, data summary, data presentation. The validity of the data is the triangulation of sources. The results of his research are Teaching Arabic at Madrasah Darul Al-Qur'an Narathiwat Thailand in terms of planning to organize teachers who are planned or summarized in teaching, while Teaching Arabic at Darul Al-Qura'an Blonxno Narathiwat Madrasah Thailand is viewed from the perspective of its implementation and implementation. mental map method in learning Arabic at Madrasah Darul Al-Qur'an Narathiwat Thailand reviewed from a hypothetical calendar after teaching directly with final evaluation at the final level.